Service delivery and ethical conduct in the public service: the missing links - Lues, L. (2007)
There are a multitude of policies, strategies and programmes directed at the rendering of effective services to the citizens of South Africa by public service managers. However, in spite of the pursuit of effectiveness and the condemning of unethical behaviour by public service managers, scandals still occur and allegations are still made. So, where are the missing links? In this article, a brief description is given of some ethical concepts viewed as important in addressing the question posed. The concluding remarks are twofold: public service organisations need to provide continuous commitment, enforcement, and modelling of leadership in professional ethics by means of, among other things, policy structures; and public service managers need to realise the importance of changing their own mindset and accepting the ethical standards that are established by the public service organisation, even if these differ from their own beliefs and culture.
Keywords: Service Delivery; Public Service Manager; Ethical Conduct